Democracia representativa y democracia participativa. Comentarios alrededor de la comparación entre la Colombia y la Venezuela contemporáneas - Stephan Launay (Desafíos, 2012)
This article seeks to demonstrate the dual nature of participatory democracy first by presenting, from a theoretical framework, some distinct features and significant differences between what is supposed to be peculiar to representative democracy and what is supposed to be part of participatory democracy, and secondly by addressing the corresponding practices of these characteristics in Venezuela and Colombia.